Celebrytyzacja polityki w opiniach wyborców - Olczyk, Tomasz (Political Preferences, 2014)
The article presents voters opinion about two aspects of political cele- britization: celebritization of style and substance of politicians' communication and politization fo celebrities. 64% of respondents sees similarities between politicians' and celebrities' communication form and content while only 22% of respondents agree with the thesis of politization of celebrities.